Sensitivity for astrophysical neutrino searches with KM3NeT-ORCA - de Wasseige, Gwenhael; Kouchner, Antoine; Molla, Marta Colomer; Dornic, Damien; Hallmann, Steffen (Proceedings of Science, 2019)
The KM3NeT facility, the next generation of large neutrino detectors, is currently being deployed in the Mediterranean Sea. KM3NeT will consist of two ARCA ("Astroparticle Research with Cosmics in the Abyss") building blocks, optimized for very high-energy astrophysical neutrinos, and of the ORCA one ("Oscillation Research with Cosmics in the Abyss"). While ORCA has originally been designed to study neutrino oscillations using atmospheric neutrinos, this dense array may also be used for astrophysical neutrino searches. We present a first estimate of the sensitivity for GeV-100GeV neutrino searches in time/space coincidence with GW alerts sent by the LIGO and Virgo collaborations (LVC). We use the final configuration of ORCA, i.e. ORCA-115 detection units, to estimate the sensitivity of ORCA to gravitational wave events that may be detected by LVC during O3.
CRIS-Team Scopus Importer:2024-12-16